Literature Review : FoMo in Digital Marketing Strategy Related to the Innovation Diffusion Process - Ratih Anggoro Wilis; Dominica A. Widyastuti (International Journal of Economics and Management Sciences, 2025)
In the ever-evolving era of digital marketing, the diffusion of innovation and the phenomenon of Fear of Missing Out (FoMO) become two interrelated elements, creating a dynamic and highly competitive marketing strategy. Diffusion of innovation, as a concept that describes the spread of new ideas or technologies in society, is a strategic key for companies that want to win the hearts of consumers. FoMO, on the other hand, is an emotional force that can be utilized as a digital marketing strategy. The fear of missing out on the latest trends or opportunities drives consumers to be more responsive to ongoing innovations. This is where the combination of innovation diffusion and FoMO creates a unique opportunity for companies. This research was conducted through a literature review study derived from 20 published journals/articles. Literature search through Google Scholar, Repect.Org, Knowledge Map, Mendeley, Schi Hub and Science Direct. The keywords used were "Fear of Missing Out" and "Diffusion of Innovation". By understanding the interplay between innovation diffusion and FoMO, companies can design digital marketing strategies that not only accelerate the adoption of new products or services, but also build communities, creating a sense of uniqueness and exclusivity that can be a powerful driver to ensure the successful launch of innovations in the fast-paced digital marketplace.